2013
DOI: 10.1111/vec.12038
|View full text |Cite
|
Sign up to set email alerts
|

Intramuscular glargine with or without concurrent subcutaneous administration for treatment of feline diabetic ketoacidosis

Abstract: Objective -To describe treatment response and outcome in 15 cats with diabetic ketoacidosis (DKA) initially stabilized with glargine administered intramuscularly (IM) with or without subcutaneous (SC) glargine. Materials and Methods -Fifteen cats diagnosed with DKA were initially administered IM glargine (1-2 U) and in most cats (12/15 cats) this was combined with SC glargine (1-3 U). This was followed by intermittent IM glargine as required at intervals of 2 or more hours (range 2-22 h) and SC glargine (1-2 U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 12 publications
3
20
0
Order By: Relevance
“…[2] Previous randomized controlled studies in patients with DKA have studied the amount and method of insulin administration required for resolution of ketoacidosis. [4,5,6] However, none of them used the CSII for managing these cases. To our knowledge, this is the first prospective randomized trial to compare the use of continuous subcutaneous insulin infusion of insulin glulisine to intravenous glulisine insulin infusion for management of mild and moderate cases of DKA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2] Previous randomized controlled studies in patients with DKA have studied the amount and method of insulin administration required for resolution of ketoacidosis. [4,5,6] However, none of them used the CSII for managing these cases. To our knowledge, this is the first prospective randomized trial to compare the use of continuous subcutaneous insulin infusion of insulin glulisine to intravenous glulisine insulin infusion for management of mild and moderate cases of DKA.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] One of the important pillars in treatment of DKA is the administration of regular insulin via intravenous (IV) infusion or by frequent subcutaneous (SC) or intramuscular (IM) injections. [4][5][6] A number of controlled trials in patients with DKA showed that low-dose insulin therapy is effective no matter by which route it was given. [7,8] Intravenous administration of regular insulin is preferred by most diabetologists because of the delayed onset of action of SC insulin and its prolonged half-life.…”
Section: Introductionmentioning
confidence: 99%
“…Diluting regular insulin 1:10 with sterile saline or special diluents available from the insulin manufacturer and using 0.3 mL U100 insulin syringes are helpful when small doses of insulin are required. Marshall, et al, (2013) recently evaluated the efficacy of IM glargine with or without concurrent SC glargine administration in fifteen cats with DKA, adapting the protocol using regular insulin described earlier. 8-22), which is an insulin concentration that inhibits lipolysis, gluconeogenesis, and glycogenolysis and promotes utilization of glucose and ketones by tissues (Kitabchi et al, 2008).…”
Section: Hourly Intramuscular Insulin Techniquementioning
confidence: 99%
“…One must remain aware of all the complicating factors in treatment and remember that fluid therapy, insulin, and potassium supplementation are the cornerstones of successful management. Diabetic remission is also possible in cats following resolution of DKA, especially in cats with concurrent pancreatic disease or cats being treated with glucocorticoids at the time DKA is diagnosed (Sieber-Ruckstuhl et al, 2008;Marshall et al, 2013). Reported in-hospital mortality rates for DKA include 29% of 21 dogs (Macintire, 1993), 30% of 127 dogs (Hume et al, 2006), and 26% of 42 cats (Bruskiewicz et al, 1997), primarily as a result of severe concurrent illness.…”
Section: Prognosismentioning
confidence: 99%
“…When insulin is administered intramuscularly (IM), it is given every hour, and blood glucose is measured every hour. 22 The availability of genetically engineered rapidly acting insulin preparations has prompted investigations into their utility for treatment of DKA. Treatment with intramuscular regular insulin is continued with 0.05 U/ kg/hr, 0.1 U/kg/hr, or 0.2 U/kg/hr if blood glucose concentration drops by more than 75 mg/dl/hr, by 50 to 75 mg/dl/hr, or by less than 50 mg/dl/hr, respectively.…”
Section: Clinical Pathologymentioning
confidence: 99%